Resilient religion, resilience and heartbreaking adversity - Hermans, C. A. M. 1955-; Schoeman, W. J. (Havertown Lit Verlag, 2023)
Cover -- Contents -- Introduction -- Chapter 1 Human experiences of heartbreaking adversity -- Chapter 2 Processes of Resilience -- Chapter 3 Resilient religion -- Chapter 4 Christian resilience, role of intellectuals, and the centrality of the god symbol: interaction and changing shape -- Chapter 5 African realities and resilient religion An invitation to Africanize the conversation -- Chapter 6 Resilient preaching A critical appraisal of Johan Cilliers' trilogy on "grace" -- Chapter 7 Becoming a Resilient Christian Community: A narrative approach -- Chapter 8 The congregation as a community of discernment and practice - enhancing resilient religion -- Chapter 9 Resilience and resistance in the Book of Job: An African socio-economic hermeneutical reading in a pandemic context -- Chapter 10 "Surviving my story of trauma": A pastoral theology of resilience -- List of contributors.
Description based on publisher supplied metadata and other sources
Keywords: Preaching; Resilience (Personality trait) - Religious aspects - Christianity; Storytelling - Religious aspects - Christianity